2013
DOI: 10.3325/cmj.2013.54.469
|View full text |Cite
|
Sign up to set email alerts
|

Gender and age differences in prevalence and incidence of child sexual abuse in Croatia

Abstract: AimTo examine age and gender differences in the prevalence and incidence of child sexual abuse, the level of acquaintance of the child and the perpetrator, and correlations between experiencing family violence and sexual abuse on a nationally representative sample of 11, 13, and 16 years old children.MethodA probabilistic stratified cluster sample included 2.62% of the overall population of children aged 11 (n = 1223), 13 (n = 1188), and 16 (n = 1233) from 40 primary and 29 secondary schools. A modified versio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 26 publications
5
25
1
2
Order By: Relevance
“…[15] In a study done in Croatia, 10.8% of the children reported as having faced some form of CSA during childhood. [16] Review conducted by Martin et al . reported that nearly 4% and 2% of girls and boys, respectively, experience CSA every year.…”
Section: Global Scenario Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…[15] In a study done in Croatia, 10.8% of the children reported as having faced some form of CSA during childhood. [16] Review conducted by Martin et al . reported that nearly 4% and 2% of girls and boys, respectively, experience CSA every year.…”
Section: Global Scenario Of the Problemmentioning
confidence: 99%
“…[346912] The overall prevalence is seen to be high among both gendersthough studies suggest girls are more prone than boys[346910111219203132], few studies report that there is no difference[16], while some others report males to be more prone. [18] In most (95%) of the cases, the perpetrator is known to the child (relatives, neighbors, step parents, highly trusted people).…”
Section: Who Are More Vulnerable To Csa?mentioning
confidence: 99%
“…Dans certaines cultures, le recours aux châtiments corporels est courant voire accepté d'un point de vue juridique 31,39 , tandis que dans d'autres cultures il s'agit d'un abus 109 . Dans certaines études, les comportements liés à l'abus sexuel n'ont pas été évalués car ce sujet a été jugé trop sensible sur le plan culturel 50,60 .…”
Section: Recension Des Enquêtes Et Des Facteurs Ayant Une Influence Sunclassified
“…Être sensible aux réactions potentielles de rejet est essentiel, tout comme l'est un énoncé clair assurant l'anonymat et la confidentialité de l'enquête. Notre revue a toutefois permis de constater que certains chercheurs avaient inclus dans le formulaire de consentement une procédure de non-respect de la confidentialité au cas où un jeune aurait besoin d'une protection, procédure permettant de l'aiguiller automatiquement vers les autorités compétentes 50,75,81 , et cette stratégie n'a pas nui au taux de réponse 75,81 .…”
Section: Considérations D'ordre éThiqueunclassified
“…Aside from reporting rates and patterns, there may be intrinsic differences between girls' and boys' experiences of CSA. While the majority of empirical CSA studies have focused on girls, there are a growing number of large‐scale community studies that have included boys and explored the influence of age and gender on children's experience of CSA (Aho et al, ; Ajdukovic et al, ; Indias Garcis and De Paúl Ochotorena, ; Radford et al, ; Sumner et al, ).…”
Section: Introductionmentioning
confidence: 99%